Efficacy and safety of adalimumab after failure of other anti-TNFα agents for plaque-type psoriasis: clinician behavior in real life clinical practice. (4th July 2019) - Esposito, Maria; Prignano, Francesca; Rongioletti, Franco; Hansel, Katharina; Bianchi, Leonardo; Pescitelli, Leonardo; Lazzeri, Linda; Ricceri, Federica; Mugheddu, Cristina; Bavetta, Mauro; Zangrilli, Arianna; Bianchi, Luca; et al.
Abstract: Introduction: During treatment with biologic agents for psoriasis (Pso) in a number of patients a failure may occur and discontinuation with transitioning to another drug or an optimization strategy, consisting in a dose-adjustment or a co-medication with a traditional systemic agent, represent two possible alternatives. Objective: The SAFARI study objective was a retrospective observation of adalimumab efficacy and safety profile after switching from other anti-TNFα agents related to clinician behavior after the failure of the first-line agent. Results: The retrospective multicenter observation demonstrated that after a first-line anti-TNFα failure adalimumab efficacy was consistent at week-12 and 24 with a further significant improvement at week-48 with a proportion of patients achieving PASI75/PASI90/PASI100 of 83.3, 71.6, and 56.9.%, respectively. Clinician strategies to extend drug-survival after first-line anti-TNFα failure, such as co-medication or dose-adjustment, were irrelevant to future drug effectiveness. Conclusions: Adalimumab profile was excellent in this 5-year retrospective observation, showing the clinical validity of interclass transitioning among anti-TNFα options.